Peripheral eosinophilia and eosinophilic bronchopneumopathy in a dog with chronic lymphocytic leukaemia. Issue 2 (19th May 2020) - Stilwell, Cecilia Alexandra; Florey, Jessica
Abstract : An eight‐year‐old, male neutered, crossbreed dog presented for evaluation of exercise intolerance, tachypnoea and cough. Initial haematology revealed moderate lymphocytosis (8.58 × 10 9 /l, reference interval (RI) 1.0–4.8) and eosinophilia (2.74 × 10 9 /l, RI 0.1–1.2). Thoracic radiographs revealed a generalised interstitial pattern with several ill‐defined nodules. Cytology of the nodules identified a mixed inflammatory population consisting of 60 per cent eosinophils. In the absence of an underlying cause, a diagnosis of eosinophilic bronchopneumopathy (EBP) was made. Five weeks after the introduction of prednisolone (2 mg/kg/day), repeated haematology revealed persistent lymphocytosis (6.89 × 10 9 /l). Blood flow cytometry was consistent with chronic lymphocytic leukaemia (CLL). Chlorambucil (6 mg/m 2 /day) was introduced and the haematological abnormalities and clinical signs resolved. The dog was euthanased 15 months after diagnosis due to acute clinical deterioration. To the authors' knowledge this is the first report of concurrent eosinophilia and EBP in a dog with CLL. The possibility of a paraneoplastic peripheral eosinophilia and EBP was considered.